Predikce pravděpodobnosti konverze uživatelů v zákazníky při dlouhé konverzní době - Materna, Jiří; Cvrk, Lubomír; Kliment, Vojtěch; Laštůvka, Jan (International Society for Science and Engineering, o.s., 2019)
Freemium business model embodies a characteristic of long period from the moment when online ad campaign brings the user to the landing page, until the moment when the user buys the product. This period is usually several orders of magnitude longer than the length of conversion period in case of buying goods, where the user performs the purchase immediately. In this article we suggest a machine learning model for long conversion periods which predicts the probability of user’s future purchase of premium services.

Freemium obchodní model z hlediska akvizice uživatelů je charakteristický tím, že od okamžiku, kdy uživatel je přiveden na cílové stránky pomocí online reklamní kampaně, do okamžiku, kdy si zakoupí produkt, zpravidla uplyne řádově delší doba než např. při nákupu zboží, kde uživatel nakoupí okamžitě. Navrhujeme zde model strojového učení, který umožní predikci pravděpodobnosti, že přivedený uživatel v budoucnosti zakoupí placené služby.
Prediction of the probability of the conversion of users to customers during a long conversion time